Revitalization and Commercialization of SMEs Products in Gampong Umong Seuribee, Aceh Besar Regency through Papaya Chips - Miswar, Edy; Kesuma, T. Meldi; Maulinda, Maulinda; Nafilaturrahmi, Nafilaturrahmi; Siregar, M. Ridha; Nisva, Raisa Ullya (Jurnal Pengabdian Bakti Akademisi, 2025)
This community service program was conducted in Gampong Umong Seuribee, Aceh Besar, to address the underutilization of abundant local papaya harvests, which were traditionally sold raw at low prices. The program aimed to revitalize and commercialize papaya as a value-added product through the production of papaya chips, thereby improving household income and fostering local entrepreneurship. Twenty-five women participated in training sessions covering hygienic food processing, appropriate use of drying and frying equipment, packaging design, and basic marketing strategies. The activities employed a participatory approach, combining demonstrations, hands-on practice, and mentoring. Results showed a significant increase in participants skills, with over 90% mastering production techniques and more than 80% ready to market the product. The initiative successfully established a distinctive village brand and created a foundation for sustainable microenterprise development, contributing to economic empowerment and aligning with sustainable development goals on poverty reduction, decent work, and responsible production.